Executive Committee Minutes 2015-06-12 - Academic Senate:::::::::
Deputy CIO for Workstation Support & IT Help Desk, Deputy CIO for Common Management Systems, Chair Report, Discussion of necessity of faculty representatives on two Admin II-level development officers for the GMC, one for annual giving, one for corporate sponsorships.